Longitudinal assessment of tricuspid regurgitation following conduction system pacing - Mitsunori Oida; Katsuhito Fujiu; Eriko Hasumi; Tsukasa Oshima; Kunihiro Kani; Kohsaku Goto; Masaki Hashimoto; Toshiya Kojima; Yu Shimizu; Kenichiro Yamagata; Gaku Oguri; Issei Komuro (Scientific Reports)
Abstract Tricuspid regurgitation (TR) is a well-known complication of pacemaker implantation (PMI). Recently, the conduction system pacing (CSP) technique, which could avoid the development of ventricular dyssynchrony, was established. However, the impact of CSP on TR is unclear. This study aimed to describe the association between CSP and worsening TR. The data of 110 patients who were given a transthoracic echocardiogram (TTE) before and after PMI were retrospectively analyzed. The severity of TR was classified into four groups. Worsening TR was defined as one or more grade increases in TR. Twenty (18.2%) patients had worsening TR, and 7 patients (6.4%) had TR ≥ moderate after PMI. After comparing the patients with and without CSP, 5 (27.8%) and 15 (16.3%) patients, respectively, had worsening TR, but the frequency did not indicate a significant difference (P = 0.25). The frequency of TR ≥ moderate after PMI in the former group was significantly higher than in the latter group at 3 (16.7%) and 4 (4.3%), respectively (P = 0.05). This study revealed that patients with CSP had a higher frequency of TR ≥ moderate after PMI compared to patients without CSP in the medium term.